A GEOGRAPHICAL ANALYSIS OF THE POPULATION AND RURAL ECONOMIC DEVELOPMENT IN THE MIDDLE BELT OF NIGERIA: A CASE STUDY FROM BIDA AND MINNA DIVISIONS OF NIGER PROVINCE (1972)
The main focus of the thesis is the examination of the factors responsible for rural economic development in a part of the Middle Belt of Nigeria. The discussion is based on the "land surplus" model and the approach is to regard population density and population growth as the independent variables which in their turn are major factors determining rural economic development in the middle Belt of Nigeria. The physical and human environment of the middle Belt and its changing economy from that of a lagging to a growing zone are discussed. The distribution, demographic and cultural characteristics of the population in different parts of the study area are shown to have influenced the socio-econonic organisation of agricultural land, labour, land use and crops grown. It is shown that the size of the population and density is below the Critical population density which the present System of land use can Support. The agricultural economy and new trends in agricultural production are discussed and it is shown that the production of food crops in the Middle Belt serves as an 'engine of growth’ (as does the production of export crops in other parts of Nigeria) in the Nigerian economy as it is a major source of food supply for the growing population and urbanization in Nigeria. The increasing integration of the Nigerian economy which has led to a greater development of the internal exchange economy in the country is shown to have aided the increasing commercialisation of food crop production in the area. In addition, population movements into the area has led to increased agricultural production. These developments have turned the Middle Belt from a lagging to a ’frontier zone’. In Order to realize the potentialities of the Middle Belt in Nigeria, a number of suggestions are made for the further development of the rural economy of the area.